The use of new communication technologies favoring the learning of science teaching in elementary school (Research, Society and Development, 2020)
This paper aims to analyze the use of New Information and Communication Technologies from the results of a qualitative research, conducted with a group of teachers of the Early Years of Elementary School of a municipality in the interior of the state of Rio de Janeiro, about the their use by teachers. The focus was the use of the notebook for the organization of lesson planning to be developed in the area of science education. The concern is about how this area of knowledge has been worked on in elementary school in the early years and it is intended to analyze the use of media resources by teachers as strategies of teaching material, taking into account the teaching practice and the interest of teachers. students in the classroom, using them. It is noteworthy that the computers were distributed to the teachers of the school units of the municipality, with the purpose of being used and explored in the organization and preparation of the lesson planning by the teachers. Thinking about the development of an interdisciplinary teaching practice and student interaction in more dynamic classes. It is understood that diversified teaching practices lead to interdisciplinary practice. This paper aims to alert to the need to improve the methodology of classroom work in the Early Years of Elementary School, regarding the use of New Communication Technologies.Keywords: Science Teaching; New Technologies; Interdisciplinary Practices.